Case report: double penile fracture - Mercado-Olivares, Felipe (2019)
Penile fracture is an underreported surgical emergency. It usually occurs as a single rupture of the tunica albuginea in one of two corpora cavernosa; a rupture of both masses is an uncommon finding. We report a case of a young male who presented to the emergency department two hours after sustaining penile trauma. Prompt surgical exploration was performed four hours post-injury. He was found to have one fracture on each corpora cavernosa, without urethral injury, which were repaired successfully. The patient had a favorable recovery and was discharged on the third postoperative day without complications. The aim of this report is to highlight the importance of complete degloving of the penile shaft for a meticulous search during surgery to avoid missed injuries. This approach will ensure a successful outcome avoiding physical and psychological disabilities.